2018
DOI: 10.1007/s12039-018-1501-9
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate entrapped caprolactam gels and their cytotoxicity study

Abstract: Polyoxometalate (POM) based gels are synthesized by reacting POMs with an excess of caprolactam. These POM-entrapped caprolactam gels are thermoreversible and possess good mechanical strength. The gelation of POMs in caprolactam matrix brought the gel acidity similar to the physiological pH. The cytotoxicity studies on SCC 131 cell lines using these gels show 50% of cell death in the range of 2 to 6 mM concentration in 48 h. The supramolecular caprolactam matrix with active protons and the redox property of PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…[46,47] Another important interaction in POM-containing supramolecular gels is hydrogen bonding, which commonly plays a key role in the system comprising of POMs and neutral organic molecules such as amino acids and peptide. [48,49] As a relative strong supramolecular interaction, a coordination bond is also powerful for building POM-containing gels in the presence of transition or rareearth metal ions. [50,51] In this case, the coordination bonds not only form between metal ions with O atoms on the surface of the cluster but also existing metal ions with N atom sourcing from functional groups anchoring on the cluster.…”
Section: Supramolecular Interactions In Pom-containing Gelsmentioning
confidence: 99%
“…[46,47] Another important interaction in POM-containing supramolecular gels is hydrogen bonding, which commonly plays a key role in the system comprising of POMs and neutral organic molecules such as amino acids and peptide. [48,49] As a relative strong supramolecular interaction, a coordination bond is also powerful for building POM-containing gels in the presence of transition or rareearth metal ions. [50,51] In this case, the coordination bonds not only form between metal ions with O atoms on the surface of the cluster but also existing metal ions with N atom sourcing from functional groups anchoring on the cluster.…”
Section: Supramolecular Interactions In Pom-containing Gelsmentioning
confidence: 99%
“…Also the feasibility of implanting the Keggin-type POMs (H 3 PM 12 O 40 , M = Mo, W) into a caprolactam matrix was reported. It was shown that decreasing the POM/caprolactam ratio enforces transformation of the resulting hybrid material from the solid to the gel-like state 85…”
Section: Pom-based Supramolecular Hybrid Compoundsmentioning
confidence: 99%
“…Both the separation and stability of the reaction process become the main problem in practical application, which greatly limits their further application in the field of photocatalysis [11,16–18] . Therefore, one rather considerable strategy is focusing on the coupling POMs with a sensitizer which is light‐collecting antennas that can capture visible light and thus improve photocatalysis performance [19,20] …”
Section: Introductionmentioning
confidence: 99%